The Differential Diagnosis and Physiotherapeutic Treatment of Piriformis Syndrome: A Systematic Review - Janaína Moraes Cardim; Diana Martins Santos; Elisangela Carneiro Quaresma; Leandro Franklim Silva Da Silva; Regina Dos Santos Silva; Renata Dos Santos Silva; Paulo Dias Rodrigues Junior; Sandriele Mougo Monteiro; Daniele Salgado; Vitor Hugo Auzier Lima (Archives of Current Research International, 2024)
Piriformis syndrome is a neuromuscular pathology that occurs when the piriformis muscle compresses the sciatic nerve, causing it to become irritated. The piriformis muscle is located in the gluteal region and originates in the anterior part of the sacrum, so piriformis syndrome is characterized by pain in the gluteal region, which can radiate to the lower limbs, being confused with symptoms of other pathologies such as herniated discs and sciatica. Piriformis syndrome can occur due to various factors, including muscle spasms, trauma, anatomical abnormalities and excessive activity. The main symptoms of this pathology include unilateral pain in the gluteal region which can radiate to the lower limb, causing muscle weakness and numbness in the affected lower limb. Diagnosing this condition is challenging, as the symptoms overlap with other musculoskeletal conditions. However, with orthopedic tests and muscle stretches, clinical examinations and imaging tests such as magnetic resonance imaging, a diagnosis can be made. Therefore, this syndrome is a condition that can affect the quality of life of affected patients, which is why physiotherapy plays an extremely important role in the treatment of this syndrome through specific therapeutic plans for each patient. This article, therefore, aims to contribute significantly to knowledge of the importance of physiotherapy in the diagnosis and treatment of piriformis syndrome, in a systematic review.